Heat conduction enhanced low-creep self-lubricating molding oil and preparation method thereof

Through the composite and process processing of materials such as PAO, LDPE, UHMWPE and fluorinated graphite, the problem of insufficient thermal conductivity of molding oil is solved, the rapid release and efficient recovery of lubricating oil are achieved, and the lubricating effect and the service life of the equipment are improved.

CN119709301APending Publication Date: 2025-03-28VONESEALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411904904.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing molding oil lacks thermal conductivity when the equipment is heated and stressed, resulting in insufficient precipitation of lubricating oil and difficult to efficiently recover lubricating oil when it is stopped, affecting the lubricating effect.

Method used

The thermally conductive and low creep self-lubricating molding oil is prepared by combining materials such as PAO, LDPE, UHMWPE and fluorinated graphite.

Benefits of technology

It significantly improves the thermal conductivity and creep resistance of molding oil, ensures that the lubricant oil is quickly released when the equipment is running and is efficiently recycled when it is stopped, improving the lubricating effect and the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005204160520000101
    Figure BDA0005204160520000101
Patent Text Reader

Abstract

The invention belongs to the field of molding oil, and particularly relates to heat conduction enhanced low-creep self-lubricating molding oil and a preparation method thereof. The heat conduction enhanced low-creep self-lubricating molding oil provided by the invention is prepared from the following raw materials in parts by mass: 60 to 80 parts of PAO, 20 to 40 parts of polyethylene, 5 to 10 parts of graphite fluoride and 0.1 to 3 parts of an antioxidant, wherein the polyethylene comprises LDPE (Low Density Polyethylene) and UHMWPE (Ultra High Molecular Weight Polyethylene), and the heat conductivity coefficient of the graphite fluoride is 200-400W / (m * K The prepared molding oil is relatively high in heat conductivity coefficient, relatively high in hardness and excellent in creep resistance, and a product has an excellent use effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of molding oil, and specifically relates to a thermally conductive enhanced low creep self-lubricating molding oil and a preparation method thereof. Background Art

[0002] In industrial scenarios where lubricants or greases are traditionally used, especially in mining machinery, textile machinery, metallurgical machinery and other equipment that are often exposed to dust, particulate pollution and humid environments, the lubricating performance of lubricants is often greatly reduced or even completely ineffective due to the intrusion of moisture and pollutants. Therefore, these equipment need to be frequently shut down for maintenance and lubricant replacement, which brings certain operation and maintenance costs to the company. In addition, affected by external factors such as gravity, the distribution of lubricants inside the equipment is often uneven, resulting in uneven lubrication effects, which will accelerate local wear of the equipment.

[0003] Molding oil, as a solid composite self-lubricating material, is compounded with lubricating oil / grease, resin and a series of additives to improve wear resistance, oxidation resistance, thermal conductivity and corrosion resistance. It can slowly and continuously release the lubricating effect between sliding / rolling friction parts and is widely used in various mechanical equipment that require lubrication. By directly contacting the molding oil with the lubricating part or installing it near it, the maintenance cycle of the equipment can be significantly extended, and even lifelong maintenance-free can be achieved, greatly reducing the operation and maintenance costs of the enterprise. The unique microporous structure of the molding oil material is composed of millions of tiny pores, so that the lubricating oil is continuously distributed in it, and the resin acts as a skeleton to provide the necessary strength. Through the action of surface tension, the lubricating oil is firmly locked inside the polymer material, forming a "plastic containing lubricating oil". During the operation of the equipment, the coupling of physical effects such as frictional heat, rotational centrifugal force and working pressure promotes the release of lubricating oil inside the molding oil material, forming a stable lubricating film, which effectively reduces friction. When the equipment stops running, the capillary effect of the micropores will suck the lubricating oil back into the hole to prevent the lubricating oil from overflowing.

[0004] The thermal conductivity of the molding oil material is crucial to the precipitation and recovery of its lubricating oil. The thermal conductivity of ordinary unmodified resin is low, usually between 0.1 and 0.5 W / (m·K). Therefore, it is a technical problem that the present invention urgently needs to solve to develop a molding oil that can quickly release lubricating oil when the equipment is heated up and stressed, and can efficiently recover lubricating oil when it stops working, and has excellent lubrication effect. Summary of the invention

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a thermally conductive enhanced low creep self-lubricating molding oil, the preparation raw materials include: lubricating base oil, polyethylene, fluorinated graphite, antioxidant.

[0006] The lubricating base oil includes: one or more of PAO, polyol ester base oil, mineral oil, hydrocracked mineral oil, alkyl naphthalene, paraffin base oil, and cycloparaffin base oil;

[0007] The dynamic viscosity of the lubricating base oil at 40°C is 20-1000 mm 2 / s.

[0008] As an implementable case, the raw materials for preparing the molding oil include, by weight, 60-80 parts of lubricating base oil, 20-40 parts of polyethylene, 5-10 parts of fluorinated graphite, and 0.1-3 parts of antioxidant.

[0009] Furthermore, the lubricating base oil is PAO (poly alpha olefin).

[0010] As an practicable example, the kinematic viscosity of the PAO at 40°C is 300-400 mm 2 / s.

[0011] As an implementable case, the thermal conductivity of the PAO is 0.11-0.16 W / (m·K).

[0012] Furthermore, the brand of PAO is DowSyn PAO40, purchased from Shanghai DowSyn Chemical Co., Ltd.

[0013] PAO has a high kinematic viscosity, and its viscosity changes little at different temperatures. The high viscosity index enables PAO to maintain good lubrication under various temperature conditions. In addition, PAO's oxidation stability is better than that of traditional base oils. It is resistant to high temperatures, has less decomposition, and has a longer service life. However, PAO's thermal conductivity and ability to resist external pollution are low, so further modification is needed to improve the thermal conductivity of the molding oil and enhance its anti-pollution ability.

[0014] As an implementable case, the polyethylene includes one or more of LDPE (low-density polyethylene), LLDPE (linear low-density polyethylene), MDPE (medium-density polyethylene), HDPE (high-density polyethylene), UHMWPE (ultra-high molecular weight polyethylene), and metallocene polyethylene.

[0015] Furthermore, the polyethylene includes LDPE and UHMWPE.

[0016] Furthermore, the mass ratio of LDPE to UHMWPE is (2-5):1.

[0017] Furthermore, the mass ratio of LDPE to UHMWPE is 3:1.

[0018] As an implementable example, the LDPE has a melt index of 50-100 g / 10 min at 190° C. / 2.16 kg.

[0019] As an implementable case, the thermal conductivity of the LDPE is 0.3-0.4 W / (m·K).

[0020] Furthermore, the grade of the LDPE is LDPE MG70, purchased from Qatar Petrochemical.

[0021] As an implementable case, the average molecular weight of the UHMWPE is 1 million to 10 million.

[0022] Furthermore, the average molecular weight of the UHMWPE is 5 million.

[0023] As an implementable case, the thermal conductivity of the UHMWPE is 0.4-0.5 W / (m·K).

[0024] Furthermore, the grade of the UHMWPE is UHMWPE U050, which is purchased from Korea Petrochemical Corporation.

[0025] UHMWPE has an extremely low friction coefficient and good self-lubricating properties. The compounded molding oil has more excellent lubricating properties, which helps to reduce friction and wear; the softness and extensibility of LDPE are also conducive to improving the lubricity of molding oil, making it easier for molding oil to distribute and penetrate between friction surfaces. The continuous lubricity of lubricating oil can be significantly improved by compounding LDPE and UHMWPE to modify PAO; LDPE gives molding oil good fluidity and ductility, while UHMWPE with an average molecular weight of 5 million enhances its wear resistance and structural strength. The synergistic effect of the two enables molding oil to maintain shape stability under low temperature and high pressure environments, reduce leakage, and improve lubrication efficiency; however, the heat resistance and creep resistance of oil-containing UHMWPE are relatively poor, so its thermal conductivity and creep resistance need to be further improved.

[0026] As an implementable example, the thermal conductivity of the fluorinated graphite is 200-400 W / (m·K).

[0027] As an implementable example, the fluorine content of the fluorinated graphite is 60-70%.

[0028] As an implementable case, the fluorine-carbon ratio of the fluorinated graphite is 1.1-1.2.

[0029] Furthermore, the brand of the fluorinated graphite is DBSF500, which is purchased from Hubei Zhuoxi Fluorination Co., Ltd.

[0030] As a high-performance additive, graphite fluoride plays a vital role in molding oil. Its high thermal conductivity (200-400W / (m·K)) ensures that heat can be transferred quickly, effectively reducing the heat accumulation caused by friction, thereby preventing overheating of the molding oil area and protecting the lubricated parts from thermal damage. The introduction of fluorine atoms gives graphite fluoride excellent chemical stability, so graphite fluoride can inhibit chemical reactions such as oxidation and corrosion, significantly extending the service life of molding oil. In harsh operating environments, the chemical stability of graphite fluoride can still be maintained, providing reliable protection for molding oil. In addition, the interlayer structure of graphite fluoride is stable, the interlayer spacing is large, and the interlayer energy is low. Therefore, graphite fluoride is easy to slide during friction and has excellent lubrication properties. It can not only significantly reduce the friction coefficient and wear rate, but also reduce the wear between mechanical parts and improve the operating efficiency and reliability of equipment. When fluorinated graphite is compounded with PAO, LDPE and UHMWPE, a significant synergistic effect is produced between them, which not only enhances the thermal conductivity of the molding oil, enabling it to quickly transfer heat and prevent friction heat accumulation, but also improves the hardness and shear resistance of the molding oil. The addition of LDPE and UHMWPE allows the molding oil to still have a certain strength under harsh conditions such as high pressure and high temperature. At the same time, the chemical stability of fluorinated graphite combined with the antioxidant properties of PAO provides excellent corrosion resistance and oxidation resistance for the molding oil, allowing the molding oil to have stable lubrication performance in harsh chemical environments and extend the service life of the equipment.

[0031] As an implementable case, the antioxidant includes: one or more of Irganox 1010, Irganox 1076, Irganox 168, Irganox 1098, Irganox 1330, Irganox 1035, and Irganox 565.

[0032] Furthermore, the antioxidant is Irganox 1010.

[0033] The second aspect of the present invention provides a method for preparing a thermally conductive enhanced low creep self-lubricating molding oil, comprising:

[0034] S1. Mix the base lubricating oil, graphite fluoride and antioxidant, add them into a stirring tank, and stir for 5-20 minutes at 100-150°C and 150-300rpm;

[0035] S2, add polyethylene, heat to 120-200℃, stir for 1-2h, and mix well;

[0036] S3, conveying the material obtained in step S2 to a storage tank, stirring at 120-200° C. and 120-200 rpm for 30-60 min, then extruding, water-cooling, pelletizing, and dehydrating to obtain molding oil particles;

[0037] S4. Dry the molding oil particles, add them into the plunger type pre-plasticizing injection molding machine for injection molding, and then use them for subsequent product processing.

[0038] Furthermore, the preparation method of the thermally conductive enhanced low creep self-lubricating molding oil comprises:

[0039] S1. PAO, graphite fluoride and antioxidant are mixed and added into a stirring tank. The mixture is stirred for 5-20 min at 100-150°C and 150-300 rpm.

[0040] S2, add an equal amount of LDPE in two batches, stir each batch for 30 minutes, heat the stirring tank to 170°C, then add an equal amount of UHMWPE in two batches, stir each batch for 30 minutes, and mix well;

[0041] S3, conveying the material obtained in step S2 to a storage tank, stirring at 120-200° C. and 120-200 rpm for 30-60 min, then extruding, water-cooling, pelletizing, and dehydrating to obtain molding oil particles;

[0042] S4. Place the molding oil particles in a dehumidification drying oven at 50-75°C for 3-5 hours, add them to a plunger type pre-plasticizing injection molding machine for injection molding, and then they can be used for subsequent product processing.

[0043] Beneficial Effects

[0044] (i) The present invention selects PAO as one of the main raw materials for preparation, mainly because PAO has good compatibility with the polyethylene carrier and its viscosity changes little at different temperatures. Therefore, the molding oil maintains a good lubricating effect under various temperature conditions.

[0045] (ii) The LDPE and UHMWPE of the present invention are compounded (lubricating oil itself has no hardness, so it is problematic to say that its hardness can be increased). The synergistic effect of the two enables the molding oil to maintain a relatively high strength under low temperature and high pressure conditions.

[0046] (III) In order to further improve the thermal conductivity of the molding oil, the present invention adds fluorinated graphite with high thermal conductivity to the raw materials for preparation. At the same time, fluorinated graphite can inhibit oxidation, corrosion and other chemical reactions, thereby significantly extending the service life of the molding oil.

[0047] (iv) Since UHMWPE has a relatively high molecular weight, the present invention adds the materials in batches during the addition, so that LDPF and UHMWPE can be completely melted and fully mixed with other materials, further improving the hardness of the molding oil.

[0048] (V) The present invention selects a plunger-type pre-plasticizing injection molding machine to prepare a high molecular weight molding oil product, mainly to solve the problem that the plastic oil with a low friction coefficient slips in the screw, resulting in the inability to perform product injection molding. DETAILED DESCRIPTION

[0049] In the following Example 1, Comparative Examples 1-6:

[0050] The PAO is of the brand DowSyn PAO40, purchased from Shanghai DowSyn Chemical Co., Ltd.

[0051] The grade of the LDPE is LDPE MG70, which is purchased from Qatar Petrochemical.

[0052] The grade of the UHMWPE is UHMWPE U050, which is purchased from Korea Petrochemical Corporation.

[0053] The grade of the graphite fluoride is DBSF500, which is purchased from Hubei Zhuoxi Fluorination Co., Ltd.

[0054] The Irganox 1010 was purchased from BASF AG.

[0055] The thermal conductivity of the carbon fiber is 1-3 W / (m·K), the brand is GX400, and it is purchased from Jilin Chemical Fiber Group Co., Ltd.

[0056] The thermal conductivity of the glass fiber is 0.1-1 W / (m·K), the grade is EMG13-125C, and it is purchased from China Jushi Co., Ltd.

[0057] Example 1

[0058] In the first aspect of this example, a thermally conductive enhanced low creep self-lubricating molding oil is provided. The raw materials used for the preparation are, by weight, 69.7 parts of PAO, 15 parts of LDPE, 5 parts of UHMWPE, 10 parts of fluorinated graphite, and 0.3 parts of Irganox 1010.

[0059] The second aspect of the present invention provides a method for preparing a thermally conductive enhanced low creep self-lubricating molding oil, which is specifically:

[0060] S1. PAO, graphite fluoride and Irganox 1010 were mixed and added into a stirring tank. The mixture was stirred at 150°C and 200 rpm for 10 min.

[0061] S2, then add an equal amount of LDPE in two batches, stir each batch for 30 minutes, then heat the stirring tank to 170°C, add an equal amount of UHMWPE in two batches, stir each batch for 30 minutes, mix well, and obtain crude molding oil;

[0062] S3, conveying the crude molding oil obtained in step S2 to a storage tank, stirring at 150° C. and 150 rpm for 30 min, then conveying the material to a water ring die face pelletizer, setting the temperature of the cooling water to 60° C., water cooling, and then dehydrating the material in a dehydrator to obtain molding oil particles;

[0063] S4. Place the molding oil particles in a dehumidification drying oven at 60°C for 3 hours, add them to a plunger-type pre-plasticizing injection molding machine for injection molding, and then proceed to the subsequent product processing; wherein the barrel temperature of the plunger-type pre-plasticizing injection molding machine is 180°C, and the mold temperature is room temperature 25°C.

[0064] Comparative Example 1

[0065] In the first aspect of this example, a thermally conductive enhanced low creep self-lubricating molding oil is provided. The raw materials used for the preparation are, by weight, 74.7 parts of PAO, 15 parts of LDPE, 10 parts of UHMWPE, and 0.3 parts of Irganox 1010.

[0066] The second aspect of the present invention provides a method for preparing a thermally conductive enhanced low creep self-lubricating molding oil, which is specifically:

[0067] S1. PAO and Irganox 1010 were mixed and added into a stirring tank. The mixture was stirred at 150°C and 200 rpm for 10 min.

[0068] S2, then add an equal amount of LDPE in two batches, stir each batch for 30 minutes, then heat the stirring tank to 170°C, add an equal amount of UHMWPE in two batches, stir each batch for 30 minutes, mix well, and obtain crude molding oil;

[0069] S3, conveying the crude molding oil obtained in step S2 to a storage tank, stirring at 150° C. and 150 rpm for 30 min, then conveying the material to a water ring die face pelletizer, setting the temperature of the cooling water to 60° C., water cooling, and then dehydrating the material in a dehydrator to obtain molding oil particles;

[0070] S4. Dry the molding oil particles in a dehumidification drying oven at 60°C for 3 hours, add them to a plunger-type pre-plasticizing injection molding machine for injection molding, and then proceed to process subsequent products; wherein the barrel temperature of the plunger-type pre-plasticizing injection molding machine is 180°C, and the mold temperature is room temperature 25°C.

[0071] Comparative Example 2

[0072] In the first aspect of this example, a thermally conductive enhanced low creep self-lubricating molding oil is provided. The raw materials used for the preparation are, by weight, 72.7 parts of PAO, 15 parts of LDPE, 10 parts of UHMWPE, 2 parts of fluorinated graphite, and 0.3 parts of Irganox 1010.

[0073] The second aspect of the present invention provides a method for preparing a thermally conductive enhanced low creep self-lubricating molding oil, which is specifically:

[0074] S1. PAO, graphite fluoride and Irganox 1010 were mixed and added into a stirring tank. The mixture was stirred at 150°C and 200 rpm for 10 min.

[0075] S2, then add an equal amount of LDPE in two batches, stir each batch for 30 minutes, then heat the stirring tank to 170°C, add an equal amount of UHMWPE in two batches, stir each batch for 30 minutes, mix well, and obtain crude molding oil;

[0076] S3, conveying the crude molding oil obtained in step S2 to a storage tank, stirring at 150° C. and 150 rpm for 30 min, then conveying the material to a water ring die face pelletizer, setting the temperature of the cooling water to 60° C., water cooling, and then dehydrating the material in a dehydrator to obtain molding oil particles;

[0077] S4. Dry the molding oil particles in a dehumidification drying oven at 60°C for 3 hours, add them to a plunger-type pre-plasticizing injection molding machine for injection molding, and then proceed to subsequent product processing; wherein the barrel temperature of the plunger-type pre-plasticizing injection molding machine is 180°C, and the mold temperature is room temperature 25°C.

[0078] Comparative Example 3

[0079] In the first aspect of this example, a thermally conductive enhanced low creep self-lubricating molding oil is provided. The raw materials used for the preparation are, by weight, 69.7 parts of PAO, 15 parts of LDPE, 5 parts of UHMWPE, 10 parts of carbon fiber, and 0.3 parts of Irganox 1010.

[0080] The second aspect of the present invention provides a method for preparing a thermally conductive enhanced low creep self-lubricating molding oil, which is specifically:

[0081] S1. PAO, carbon fiber and Irganox 1010 were mixed and added into a stirring tank. The mixture was stirred at 150°C and 200 rpm for 10 min.

[0082] S2, then add an equal amount of LDPE in two batches, stir each batch for 30 minutes, then heat the stirring tank to 170°C, add an equal amount of UHMWPE in two batches, stir each batch for 30 minutes, mix well, and obtain crude molding oil;

[0083] S3, conveying the crude molding oil obtained in step S2 to a storage tank, stirring at 150° C. and 150 rpm for 30 min, then conveying the material to a water ring die face pelletizer, setting the temperature of the cooling water to 60° C., water cooling, and then dehydrating the material in a dehydrator to obtain molding oil particles;

[0084] S4. Dry the molding oil particles in a dehumidification drying oven at 60°C for 3 hours, add them to a plunger-type pre-plasticizing injection molding machine for injection molding, and then proceed to the subsequent product processing; wherein the barrel temperature of the plunger-type pre-plasticizing injection molding machine is 180°C, and the mold temperature is room temperature 25°C.

[0085] Comparative Example 4

[0086] In the first aspect of this example, a thermally conductive enhanced low creep self-lubricating molding oil is provided. The raw materials used for the preparation are, by weight, 69.7 parts of PAO, 15 parts of LDPE, 5 parts of UHMWPE, 10 parts of glass fiber, and 0.3 parts of Irganox 1010.

[0087] The second aspect of the present invention provides a method for preparing a thermally conductive enhanced low creep self-lubricating molding oil, which is specifically:

[0088] S1. PAO, glass fiber and Irganox 1010 were mixed and added into a stirring tank. The mixture was stirred at 150°C and 200 rpm for 10 min.

[0089] S2, then add an equal amount of LDPE in two batches, stir each batch for 30 minutes, then heat the stirring tank to 170°C, add an equal amount of UHMWPE in two batches, stir each batch for 30 minutes, mix well, and obtain crude molding oil;

[0090] S3, conveying the crude molding oil obtained in step S2 to a storage tank, stirring at 150° C. and 150 rpm for 30 min, then conveying the material to a water ring die face pelletizer, setting the temperature of the cooling water to 60° C., water cooling, and then dehydrating the material in a dehydrator to obtain molding oil particles;

[0091] S4. Dry the molding oil particles in a dehumidification drying oven at 60°C for 3 hours, add them to a plunger-type pre-plasticizing injection molding machine for injection molding, and then proceed to the subsequent product processing; wherein the barrel temperature of the plunger-type pre-plasticizing injection molding machine is 180°C, and the mold temperature is room temperature 25°C.

[0092] Comparative Example 5

[0093] In the first aspect of this example, a thermally conductive enhanced low creep self-lubricating molding oil is provided. The raw materials used for the preparation are, by weight, 89.7 parts of PAO, 5 parts of LDPE, 5 parts of UHMWPE, and 0.3 parts of Irganox 1010.

[0094] The second aspect of the present invention provides a method for preparing a thermally conductive enhanced low creep self-lubricating molding oil, which is specifically:

[0095] S1. PAO and Irganox 1010 were mixed and added into a stirring tank. The mixture was stirred at 150°C and 200 rpm for 10 min.

[0096] S2, then add an equal amount of LDPE in two batches, stir each batch for 30 minutes, then heat the stirring tank to 170°C, add an equal amount of UHMWPE in two batches, stir each batch for 30 minutes, mix well, and obtain crude molding oil;

[0097] S3, conveying the crude molding oil obtained in step S2 to a storage tank, stirring at 150° C. and 150 rpm for 30 min, then conveying the material to a water ring die face pelletizer, setting the temperature of the cooling water to 60° C., water cooling, and then dehydrating the material in a dehydrator to obtain molding oil particles;

[0098] S4. Dry the molding oil particles in a dehumidification drying oven at 60°C for 3 hours, add them to a plunger-type pre-plasticizing injection molding machine for injection molding, and then proceed to the subsequent product processing; wherein the barrel temperature of the plunger-type pre-plasticizing injection molding machine is 180°C, and the mold temperature is room temperature 25°C.

[0099] Comparative Example 6

[0100] In the first aspect of this example, a thermally conductive enhanced low creep self-lubricating molding oil is provided. The raw materials used for the preparation are, by weight, 59.7 parts of PAO, 20 parts of LDPE, 20 parts of UHMWPE, and 0.3 parts of Irganox 1010.

[0101] The second aspect of the present invention provides a method for preparing a thermally conductive enhanced low creep self-lubricating molding oil, which is specifically:

[0102] S1. PAO and Irganox 1010 were mixed and added into a stirring tank. The mixture was stirred at 150°C and 200 rpm for 10 min.

[0103] S2, then add an equal amount of LDPE in two batches, stir each batch for 30 minutes, then heat the stirring tank to 170°C, add an equal amount of UHMWPE in two batches, stir each batch for 30 minutes, mix well, and obtain crude molding oil;

[0104] S3, conveying the crude molding oil obtained in step S2 to a storage tank, stirring at 150° C. and 150 rpm for 30 min, then conveying the material to a water ring die face pelletizer, setting the temperature of the cooling water to 60° C., water cooling, and then dehydrating the material in a dehydrator to obtain molding oil particles;

[0105] S4. Dry the molding oil particles in a dehumidification drying oven at 60°C for 3 hours, add them to a plunger-type pre-plasticizing injection molding machine for injection molding, and then proceed to the subsequent product processing; wherein the barrel temperature of the plunger-type pre-plasticizing injection molding machine is 180°C, and the mold temperature is room temperature 25°C.

[0106] Performance Evaluation

[0107] 1. Thermal conductivity test

[0108] Test objects: molding oils prepared in Example 1 and Comparative Examples 1-6.

[0109] Test method: The heat transfer coefficient test was carried out with reference to GB / T 22588, where the size of the thermal conductivity test block was: 50 mm (length) × 50 mm (width) × 2 mm (thickness). The test results are detailed in Table 1.

[0110] 2. Compression creep performance test

[0111] Test objects: molding oils prepared in Example 1 and Comparative Examples 1-6.

[0112] Test method: The molding oil was compressed for 48 hours at a temperature of 80°C and a pressure of 20 kPa, and the compression creep performance was tested with reference to GB / T22588. The size of the compression creep test block was 50 mm (length) × 50 mm (width) × 20 mm (thickness). The test results are shown in Table 1.

[0113] 3. Hardness test

[0114] Test objects: molding oils prepared in Example 1 and Comparative Examples 1-6.

[0115] Test method: Hardness test was carried out in accordance with GBT 531.1-2008. The test results are shown in Table 1.

[0116] Table 1

[0117]

[0118] As demonstrated by the above-mentioned Example 1 and Comparative Examples 1-6, selecting a compound of 60-80 parts of PAO, 20-40 parts of polyethylene, 5-10 parts of fluorinated graphite, and 0.1-3 parts of antioxidant can effectively improve the hardness, thermal conductivity and creep resistance of the molding oil.

Claims

1. A thermally conductive, enhanced, low creep, self-lubricating molding oil, characterized in that: The preparation raw materials include: lubricating base oil, polyethylene, fluorinated graphite, antioxidant; The lubricating base oil includes: one or more of PAO, polyol ester base oil, mineral oil, hydrocracked mineral oil, alkyl naphthalene, paraffin base oil, and cycloparaffin base oil; The dynamic viscosity of the lubricating base oil at 40°C is 20-1000 mm 2 / s.

2. The thermally conductive enhanced low creep self-lubricating molding oil according to claim 1, characterized in that: The raw materials for preparing the molding oil include, by weight, 60-80 parts of lubricating base oil, 20-40 parts of polyethylene, 5-10 parts of fluorinated graphite, and 0.1-3 parts of antioxidant.

3. The thermally conductive enhanced low creep self-lubricating molding oil according to claim 1, characterized in that: The polyethylene includes: one or more of LDPE, LLDPE, MDPE, HDPE, UHMWPE, and metallocene polyethylene.

4. The thermally conductive enhanced low creep self-lubricating molding oil according to claim 3, characterized in that: The polyethylene includes LDPE and UHMWPE, and the mass ratio of LDPE to UHMWPE is (2-5):

1.

5. The thermally conductive enhanced low creep self-lubricating molding oil according to claim 4, characterized in that: The melting index of the LDPE under the condition of 190°C / 2.16kg is 50-100g / 10min.

6. The thermally conductive enhanced low creep self-lubricating molding oil according to claim 4, characterized in that: The average molecular weight of the UHMWPE is 1 million to 10 million.

7. The thermally conductive enhanced low creep self-lubricating molding oil according to any one of claims 1 to 6, characterized in that: The thermal conductivity of the fluorinated graphite is 200-400 W / (m·K).

8. The thermally conductive enhanced low creep self-lubricating molding oil according to claim 7, characterized in that: The fluorine content of the fluorinated graphite is 60-70%.

9. The thermally conductive enhanced low creep self-lubricating molding oil according to claim 7, characterized in that: The fluorine-to-carbon ratio of the fluorinated graphite is 1.1-1.

2.

10. A method for preparing the thermally conductive enhanced low creep self-lubricating molding oil according to any one of claims 1 to 9, characterized in that: include: S1. Mix the base lubricating oil, graphite fluoride and antioxidant, add them into a stirring tank, and stir for 5-20 minutes at 100-150°C and 150-300rpm; S2, add polyethylene, heat to 120-200°C, stir for 1-2h, mix well, and obtain crude molding oil; S3, conveying the crude molding oil obtained in step S2 to a storage tank, stirring at 120-200° C. and 120-200 rpm for 30-60 min, and then extruding, water-cooling, pelletizing, and dehydrating to obtain molding oil particles; S4. Dry the molding oil particles, add them into the plunger type pre-plasticizing injection molding machine for injection molding, and then proceed to the subsequent product processing.